2013
DOI: 10.1002/jsfa.6171
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of grape by‐product‐fortified breads against cholesterol/cholic acid diet‐induced hypercholesterolaemia in rats

Abstract: These results demonstrate that intake of both PGP- and EGP-fortified sourdough mixed rye breads might contribute to a reduction of cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…This may suggest that RB or TP act mainly through reducing intestinal lipid absorption. Similarly, in the study conducted by Mildner‐Szkudlarz and Bajerska, the intake of mixed bread enriched with 6% dried powdered skins of grape by‐products significantly increased faecal fat, decreasing the apparent digestion of fat . The reduction of lipid absorption in the small intestine may be caused by soluble fibre, particularly by viscous or gel‐forming soluble fibre .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This may suggest that RB or TP act mainly through reducing intestinal lipid absorption. Similarly, in the study conducted by Mildner‐Szkudlarz and Bajerska, the intake of mixed bread enriched with 6% dried powdered skins of grape by‐products significantly increased faecal fat, decreasing the apparent digestion of fat . The reduction of lipid absorption in the small intestine may be caused by soluble fibre, particularly by viscous or gel‐forming soluble fibre .…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, in the study conducted by Mildner-Szkudlarz and Bajerska, the intake of mixed bread enriched with 6% dried powdered skins of grape by-products significantly increased faecal fat, decreasing the apparent digestion of fat. 38 The reduction of lipid absorption in the small intestine may be caused by soluble fibre, particularly The values in the table represent means ± SD of 10 rats. Means with different letters differ significantly at P < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…An automated blood biochemical analyser (Fuji Dri‐Chem 3500, Tokyo, Japan) was used to measure the liver function enzymes, AST (Aspartate Aminotransferase) and ALT (Alanine Aminotransferase). The atherogenic index (AI) was calculated as TC‐HDL‐C/HDL‐C (Mildner‐Szkudlarz & Bajerska, ). Microsomes were separated from the liver, after which the microsomal protein and HMG‐CoA reductase activity were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Hyperlipidaemia and increase in low-density lipoprotein cholesterol (LDL-C) are the major causes of atherosclerosis, which could increase the death rate from cardiovascular disease (CVD; Jones, 2009). High levels of triglyceride, total cholesterol and LDL-C in the blood can induce hypercholesterolaemia, hypertension, stroke, lipid peroxidation and obesity (Li et al, 2013;Mildner-Szkudlarz & Bajerska, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Degradation during storage may also induce a relevant decrease in phenolic content. Mildner‐Szkudlarz and Bajerska () reported that breads enriched with freeze‐dried wine pomace made from skin reduced total cholesterol levels, low‐density lipoprotein, lipid peroxidation, and increased antioxidant activity in rats with diet‐induced hypercholesterolemia. Recently, grape seed extract incorporated into white bread was proposed to reduce the postprandial glycemic response and increase satiety (Coe and Ryan ).…”
Section: Functions In the Food Industrymentioning
confidence: 99%